Custos de transporte e armazenagem de cafés commodities e especiais - Soares, Giancarlo Fernandes (2022)
Coffee is a wealth of Brazilian agriculture and can be a commodity or a special coffee. This study aimed to verify the effects generated by transport and storage in the coffee crop, in relation to the cost and price paid to the rural producer in the commodity coffee and in the special coffee of the Cerrado Mineiro region. For this, a producer was interviewed, 32 years ago in the market, for which we asked about the transport and storage of coffee from Cerrado Mineiro. To verify whether there is statistical variance between the price of coffee and transport and storage costs and, if they are different between the two coffee specialties, the use of Pearson and Student t tests was considered, and the t-test was performed for data with normal distributions, which were tested using the Shapiro-Wilk test. The results indicate that the transport variable was close in commodity and specialty coffees, the storage variable had a greater impact on the final selling price in commodity and specialty coffees, due to the different types of care to ensure grain quality. It is thus concluded that transport and storage are among the highest costs of coffee producers, but investments in specialty coffees are converted into benefits for the rural producer because they are valued in the final price per bag of 60Kg.